1998
DOI: 10.1097/00006982-199805000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice with Increased Expression of Vascular Endothelial Growth Factor in the Retina: A New Model of Intraretinal and Subretinal Neovascularization.

Abstract: Vascular endothelial growth factor (VEGF) has been implicated in retinal neovascularization (NV), but it has been difficult to produce retinal NV with exogenous VEGF. We investigated the effect ofincreased VEGF expression in the retina using tissue-specific, gain-of-function transgenic mice in which the bovine rhodopsin promoter is coupled to the gene for human VEGF New blood vessel formation or neovascularization (NV) is essential for normal eye development, but it can also cause severe ocular disease. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
329
1
7

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(347 citation statements)
references
References 8 publications
10
329
1
7
Order By: Relevance
“…In situ hybridization analyses showed the proliferation of blood vessels to be accompanied by an induction of retinal VEGF expression only in the retinal layer effected by decreased perfusion (Pe'er et al, 1995). Also, transgenic mice with overexpression of VEGF in the photoreceptor layer develop intraretinal and subretinal neovascularization (Okamoto et al, 1997). In a single report in the literature, in situ hybridization studies of an autopsy specimen with stage 3 ROP showed increased VEGF mRNA expression in the peripheral avascular region in the ganglion cell layer and inner nuclear layer, confirming the results from the animal studies described below (Young et al, 1997).…”
Section: Vegf and Abnormal Retinal Vascularizationsupporting
confidence: 53%
“…In situ hybridization analyses showed the proliferation of blood vessels to be accompanied by an induction of retinal VEGF expression only in the retinal layer effected by decreased perfusion (Pe'er et al, 1995). Also, transgenic mice with overexpression of VEGF in the photoreceptor layer develop intraretinal and subretinal neovascularization (Okamoto et al, 1997). In a single report in the literature, in situ hybridization studies of an autopsy specimen with stage 3 ROP showed increased VEGF mRNA expression in the peripheral avascular region in the ganglion cell layer and inner nuclear layer, confirming the results from the animal studies described below (Young et al, 1997).…”
Section: Vegf and Abnormal Retinal Vascularizationsupporting
confidence: 53%
“…The fusion gene was purified and transgenic mice were generated as previously described. 27 Mice were screened by polymerase chain reaction (PCR) of tail DNA using an upstream primer in the TRE domain (GAC CTC CAT AGA AGA CAC CG) and a downstream primer in the ang1 domain (CCT ATG TGA GTC AGA ATG GC) that amplify a 500 bp transgenespecific product. Tail DNA was obtained by overnight digestion of a 2 mm tail segment in 0.5 mg/ml proteinase K, 10 mmol/l Tris-HCl, pH 7.5, 100 mmol/l NaCl, 20 mmol/l ethylenediaminetetraacetic acid, and 2% Triton X-100 at 551C.…”
Section: Generation Of Double Transgenic Mice With Inducible Expressimentioning
confidence: 99%
“…25 Mice from the V-6 line that are heterozygous for the rhodopsin/VEGF transgene develop NV that originates from the deep capillary bed of the retina and grows into the subretinal space, where it gradually spreads and enlarges. V-6 rho/VEGF mice were mated with rho/PDGF-A2 or rho/PDGF-A3 mice and, at P21, the offspring were perfused with fluorescein-labeled dextran, and retinal NV was measured on retinal flat mounts as previously described.…”
Section: Compound Transgenic Mice With Increased Expression Of Both Pmentioning
confidence: 99%